BURKITT LYMPHOMA WITH ABERRANT IMMUNOPHENOTYPE IMPOSING DIAGNOSTIC CHALLENGE - Mansoor, Neelum; Nausheen Yaqoob,; Fatima Meraj,; Naeem Jabbar,; Saba Jamal, (Journal of Ayub Medical College Abbottabad, 2021)
Background: Burkitt lymphoma (BL) exhibits a characteristic immunophenotype that is positive for pan-B-cell antigens and germinal center markers while negative for immature markers. A deviation from classic immunophenotype can cause diagnostic confusion and might result in false exclusion of BL. In some cases, overlapping clinical, morphological and immunophenotypic features of BL and B lymphoblastic lymphoma (B-LL) can be of diagnostic challenge. However, definitive delineation is of paramount importance due to difference in treatment. We describe a case of BL in a child with atypical features including absence of L3 morphology in diagnostic tissue and aberrant expression of CD34, CD99 and BCL2 on immunohistochemistry. These findings led to the interpretation of B-LL which was later on excluded by detection of t (8;14). This unorthodox case not only highlights the importance of cytogenetic testing but also emphasizes the correlation of all the diagnostic tools before making a definitive diagnosis. Therefore, reporting this case will help in eliciting the high index of suspicion among pathologists for this exceptionally unusual immunophenotype.